Manoel Luiz Reefs morphology unveiled by high resolution satellite images (North Brazilian Continental Shelf) - Tavares de Macedo Dias, Gilberto; Cuellar de Oliveira e Silva, Rafael; dos Santos Filho, João Regis (Quaternary and Environmental Geosciences, 2021)
The reefs of Manoel Luiz are located 100 nautical miles N from the city of São Luís, capital of the State of Maranhão - Brazil. The region is practically unconquerable, due to the great concentration of shallow reef pinnacles; it has never been possible to map the area by traditional methods, due to the dangers to navigate. The images acquired in June 2018, by programmed WorldView-3 satellite (30 cm resolution), revealed for the first time the real and exuberant reef formation with innumerable constructions, predominantly individual with circular, or linear and coalescent format. The reefs of Manoel Luiz are not constructed by corals. Drop-camera videos shows that sparse colonies of corals are fixed on hard structures formed (covered) by superimposed crusts of calcareous algae. The location of Manoel Luiz reefs remained almost 300 years unknown to navigators, since the year 1500, attributed to the discovery of Brazil, until 1820, when it was described by the French hydrographer Adm. Baron de Roussin, and another 198 years to be precisely georeferenced and mapped.